1999
DOI: 10.1039/a807381c
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative study to improve the quality control of rare earth element determinations in environmental matrices

Abstract: In order to control the quality of rare earth determinations in environmental matrices, the Standards, Measurements and Testing Programme (formerly Community Bureau of Reference, BCR) of the European Commission has started a project, the final aim of which is to certify four types of matrices (tuna muscle, mussel tissue, aquatic plant and estuarine sediment) for their contents of a range of rare earth elements (Sc, Y and the lanthanides: La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu). The elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…nvironmental effects of rare earth elements (REEs), namely lanthanides, have become of great concern owing to their increasing use in industrial products and agriculture [1,2]. REEs also serve as analogs for the actinide elements (Am and Cm), such that the accurate determination of REEs at low levels is likewise important for predicting the behavior of the radioactive actinides in future radioactive waste repositories [3].…”
mentioning
confidence: 99%
“…nvironmental effects of rare earth elements (REEs), namely lanthanides, have become of great concern owing to their increasing use in industrial products and agriculture [1,2]. REEs also serve as analogs for the actinide elements (Am and Cm), such that the accurate determination of REEs at low levels is likewise important for predicting the behavior of the radioactive actinides in future radioactive waste repositories [3].…”
mentioning
confidence: 99%
“…I 23 2.7 Material Coilection and Preparation a1 reports (Berman 1985;European Commission 1994;Gardiner 1993;Ihnat 1988aIhnat , 1988bIhnat , 1988cIhnat , 1994; Ihnat and Wolf 1985;Ihnat et al 1987;IO-arner GN et al 1993Kramer KJM et al 1999;Quevauviller et al 1998a;Roper et al 1999;Schladot et al 1993;Zeisler and Wise 1985). Most of these have an overwhelming impact on the finally developed RM and on its credibility.…”
Section: Introductionmentioning
confidence: 99%
“…(1990);Schladot et al (1993);Fraser et al (1995);Quevauviller et al, 1998dKramer et al (1999Morabito et al (1999) Bowen (1965;Ihnat and Wolf (1985); Becker and Gills; Quevauviller et al (1998b); Zeisler et al (1998) Ihnat et al (1987); Ihnat (1988); Jerome (1993); Zeisler et al (1993); Quevauviller et a1 ( 1 9 9 8~ 1998f, 1998g); Sharpless et al (1999) Yeoman et al (1985); Versieck et al (1987); Quevauviller et a1 (1992a, 1998e); Stone et al (1995); Yoshinaga et al (1997) Mooijrnaii et al (1992) Heller-Zeisler et al (1998); Quevauviller et al (1998, 1999) Griepink et al (1991); Vercoutere et al (1995); Quevauviller et al National Research Council Canada (1992); Quevauviller et al (~y p b , 1996); Merry (1995); Benolie1 et al (1997); Quevauviller et al (1998h, 1998k) Lister (1978) Bowman et a]. (1979); LaBrecque (1990); Vercoutere et al (1995); Quevauviller et al (1998m, 1998k) Olcamoto and Iwata (1982); Berkovits and Lukashin (1884); Epstein et al (1989); Schantz et al (1990); Bowman (1994) Gonska et al (1984) Zaichick (1995); Bogershausen et al (1997) (1998h 19981~) Griepink et al (1981); Marchandise and Vandendriessche…”
mentioning
confidence: 99%
“…Incomplete dissolution of highly resistant minerals in sediments, soils, and rocks may cause biased results for a number of elemental analyses. An interesting program for preparation and certification of reference samples, coordinated by the Community Bureau of Reference (BCR), showed that significant differences were found in the REE concentration results in sediment and soil samples, by employing or not, HF and also by fusion (Kramer et al 1999;Kramer et al 2002).…”
mentioning
confidence: 99%
“…Naturally, the use of HF implies the use of Teflon flasks that can be open or, in order to reduce the time required for sample preparation, sealed pumps, at high pressure and high temperatures (>160 C), obtained by microwave or conventional heating (Yu, Robinson, and McGoldrick 2001). According to Kramer et al (1999Kramer et al ( , 2002, the use of HF is essential for silicate dissolution and accurate quantification of REE in geological samples, such as sediment and soil. However, REE, as well as other elements, can coprecipitate with Ca, Mg, and Al, also present in mineral samples, which form fluoride complexes (Yokoyama, Makishima, and Nakamura 1999;Tanaka et al 2003;Lu, Makishima, and Nakamura 2007).…”
mentioning
confidence: 99%